STUDENTS’ PERCEPTION ON THE USE OF A LECTURER’S BILINGUAL APPROACH IN INTERNATIONAL CLASS PROGRAM (ICP) CHEMISTRY EDUCATION DURING THE COVID-19 RESTRICTIONS - Nurinayah Ramadhani; A. Muliati; Chairil Anwar Korompot (Universitas Negeri Makassar, 2022)
The aims of this research were: (1) to find out how the students perceive the use of a lecturer’s bilingual approach in ICP chemistry education during the covid-19 restrictions; (2) and to find out how the lecturer applies the bilingual approach in ICP chemistry education during the covid-19 restriction. This research used a qualitative method. The participants in this research were 14 students of the 3rd-semester ICP chemistry education, State University of Makassar. The instrument of the research was an interview that was conducted online. The results of the research showed that (1) the students perceived that the lecturer’s use of the bilingual approach in ICP chemistry education during the covid-19 restrictions was favorable; and (2) the lecturer applied the bilingual approach in written English, spoken English, and bahasa Indonesia. The written English is used in a Microsoft PowerPoint presentation, spoken English when the lecturer explains the material, and starts using bahasa Indonesia when the students cannot understand the English explanation. However, the dominant language that the lecturer used is bahasa Indonesia. There is no different method that the lecturer uses in applying a bilingual approach in ICP chemistry education during the covid-19 restriction